I'll give brainliest and extra points if someone helps me with all the questions!!
![Ill give brainliest and extra points if someone helps me with all the questions class=](https://us-static.z-dn.net/files/d11/01610ba492a1f1ba7016794ee7ed3085.png)
Answer:
2x-y=0
Step-by-step explanation:
By using two points form:
[tex]\frac{y-y_{1} }{y_{2}-y_{1} }[/tex]=[tex]\frac{x-x_{1} }{x_{2}-x_{1} }[/tex]
x1=-1 , x2=2 , y1=-2 ,y2=4
Substitute the values in the formula above:
[tex]\frac{y+2}{4+2}[/tex]=[tex]\frac{x+1}{2+1}[/tex]
[tex]\frac{y+2}{6}[/tex]=[tex]\frac{x+1}{3}[/tex]
2(x+1)=y+2
2x+2=y+2
2x-y=0